STRATEGI PEMBERDAYAAN USAHA KECIL DAN MENENGAH SEKTOR PERTANIAN DALAM MENDUKUNG SEKTOR PARIWISATA DI PROVINSI BALI - IDA BAGUS KETUT SURYA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2007)
ABSTRACT The Balinese economy is full of unregulated small and medium sized family businesses. This sector provides employment opportunities to low-skilled and under-educated workers. Generally, these businesses contribute significantly to the county’s gross domestic product. It is the government’s policy to give a large priority to the development of these small, medium and family businesses because of the influence they have on the level of employment. With further development, these businesses can provide a strong foundation for the Indonesian economic structure, and specifically Bali’s. The purposes of the research are: (1) To identify how tourism stimulates the farming sub sector. (2) To identify the type and quantity of vegetables needed by the tourism sector in Bali. (3) To plan a strategic program for small vegetable business development for in the Bali province. The findings from the analysis were: 1. In the farming production sector the plants sub sector has a stronger correlation with tourism than the other sub-sectors such as agriculture, animal farming, forestry, and fish farming. The plant sub sector is split into fruit and vegetable, with the vegetables accounting for twice as much of the production at 0,0031% with the elasticity at 2,05%. This makes vegetables the most important crop in relation to the tourism sector in Bali. 2. The type and quantity of vegetables needed by tourism are as follows: 1) Statistics show that the vegetables needed by the hotel, restaurant, and food stalls in the following five regencies of Bali, Gianyar, Buleleng, Bangli, Tabanan, and Karangasem, is around 391.765 ton. These regencies account for 50% of the vegetable need in Bali so the total need for the tourism industry in Bali is approximately 783.530 ton per year. In 2003 the total vegetable for the whole of Bali was 269.562 ton, which means there is a deficit of 513.868 ton in the tourism sector, without even factoring in the domestic demand. 2) There are fifteen types of vegetable which are mainly needed by the tourism sector: onion, garlic, chilies, tomatoes, potatoes, cabbage, carrot, green vegetable, runner beans, water spinach, spinach, cucumber, beans, salads, and parsley. 3) Most hotels buy their vegetables through a contract system, but most restaurants and food stalls buy from the traditional markets. 4) Most hotels, restaurants and food stalls supply their vegetables daily at the percentage of 71, 83% and incidentally at 28, 17% and 3. The required strategies to improve small and medium sized vegetable businesses are: 1) Small medium vegetable producer’s business strategic plan such as: (1) To improve the minimum vegetable production levels; (2) To improve product competition; (3) Sub terminal agro business development; (4) To improve the safety of Bali as a tourism destination; (5) To improve the quality of the vegetables produced; (6) To provide economic support and allowances for the small and medium farming businesses; (7) Encourage partnerships between small and medium vegetable businesses, suppliers, and hotels. 2) Small medium vegetable trader’s business strategic plan such as: (1) Improve the consistency and quantity of supply to hotels and supermarkets; (2) Improve the ability to adapt with changes; (3) Develop different products and product quality; (4) Partnership between small medium vegetable trader’s business with hotels and supermarkets; (5) Improve the business management; (6)Make a strong position for small medium vegetable businesses to support the tourism market; (7) Improve the ability to compete; (8) Create price stability. Key words: Small medium business improvement, Farming section, Tourism support ABSTRAK Usaha kecil-menengah (UKM) dan usaha rumah tangga (URT) yang tidak berbadan hukum adalah pelaku-pelaku ekonomi Bali, tersebar di semua sektor ekonomi, merupakan usaha yang banyak menciptakan lapangan usaha tanpa harus mempunyai jenjang pendidikan tertentu atau keahlian khusus. Secara nasional kontribusi jenis usaha ini terhadap produk domestik bruto sangat signifikan. Kebijakan pemerintah untuk memberi prioritas lebih besar dalam pembangunan yang berorientasi pada pemberdayaan ekonomi kerakyatan utamanya UKM dan URT sangat strategis dan akan berdampak luas terhadap penyerapan tenaga kerja. Ke depan jenis usaha semacam ini menjadi fondasi yang cukup kokoh bagi struktur perekonomian Indonesia umumnya dan perekonomian Bali khususnya. Tujuan penelitian yaitu: (1) Mengidentifikasi sub-sub sektor pertanian pendukung pariwisata, (2) MengiIdentifikasi jenis dan kuantitas sayuran yang dibutuhkan sektor pariwisata di Bali, dan (3) Merumuskan strategi dan program pemberdayaan UKM sayuran di Popinsi Bali Dari hasil analisis diperoleh temuan penting sebagai berikut: 1. Pada kelompok sektor produksi pertanian dalam arti luas, sub sektor tanaman pangan memiliki keterkaitan paling kuat dengan pariwisata dibandingkan dengan sub sektor lainnya seperti perkebunan, peternakan, kehutanan dan perikanan. Sedangkan pada kelompok produksi sub sektor tanaman pangan, sub-sub sektor sayuran memiliki pengganda terbesar kedua setelah buah-buahan, ditunjukkan oleh pengganda dan elastisitas masing-masing sebesar 0,031 dan 2,05%. Ini mengindikasikan bahwa sub-subsektor sayuran berperan menunjang sektor pariwisata di Bali, terutama dalam memenuhi kebutuhan wisatawan akan sayuran, 2. Jenis dan Jumlah sayuran yang dibutuhkan oleh pariwisata: 1) Kebutuhan sayuran oleh hotel, restoran dan rumah makan di lima kabupaten di Bali yaitu Gianyar, Buleleng, Bangli, Tabanan dan Karangasem sebanyak 391.765 ton, diperkirakan hanya 50% dari total kebutuhan sayuran di Bali. Jika demikian halnya, total kebutuhan sayuran oleh hotel, restoran dan rumah makan di Bali diperkirakan sebanyak 783.530 ton per tahun. Sedangkan produksi sayuran di Bali tahun 2003 sebesar 269.562 ton, berarti produksi sayuran di Bali masih defisit sebesar 513.968 ton per tahun dibandingkan dengan kebutuhan pariwisata. 2) Jenis sayuran yang dibutuhkan mencakup 15 jenis, yaitu Bawang Merah, Bawang Putih, Lombok, Tomat, Kentang, Kubis, Wortel, Sawi Hijau/Petsai, Kacang Panjang, Kangkung, Bayam, Mentimun, Buncis, Selada dan Parsely, 3) Sistem pengadaan sayuran oleh hotel-hotel melalui sistem kontrak, sedangkan oleh restoran dan rumah makan melalui sistem pembelian langsung ke pasar-pasar tradisional, 4) Sebagian besar kontinuitas pengadaan sayuran oleh hotel, resatoran dan rumah makan secara harian (71,83%), sedangkan hanya sebagian kecil (28,17%) secara insidental; dan 3. Strategi Pemberdayaan potensi UKM Sayuran yaitu: 1). Strategi Pemberdayaan UKM produsen (petani sayuran), yaitu: (1) Meningkatkan produksi sayuran minimum khemikalia; (2) Meningkatkan daya saing produk; (3) Pemberdayaan sub terminal agribisnis; (4) Meningkatkan keamanan daerah wisata; (5) Pemberdayaan petani sayuran; (6) Memperkuat posisi UKM petani; (7) Pola kemitraan antara UKM petani, pengepul dan hotel, dan 2) . Strategi pemberdayaan UKM pedagang sayuran antara lain: (1) Meningkatkan kemampuan kuantitas dan kontinuitas memasok hotel dan swalayan; (2) Peningkatan kemampuan adaptasi terhadap perubahan; (3) Peningkatan keragaman dan kualitas produk; (4) Kemitraan antara UKM pedagang sayuran dengan hotel dan swalayan; (5) Peningkatan manajemen usaha; (6) Memperkuat posisi UKM sayuran menunjang pasar pariwisata; (7) Meningkatkan kemampuan bersaing; (8) Stabilisasi harga. Kata kunci: Pemberdayaan UKM, Sektor Pertanian, Mendukung Pariwisata.